2017
DOI: 10.1021/acs.est.7b02860
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Formation Induced by the Impact of Reactive Bromine and Iodine Species on Photochemistry in a Polluted Marine Environment

Abstract: Reactive iodine and bromine species (RIS and RBS, respectively) are known for altering atmospheric chemistry and causing sharp tropospheric ozone (O) depletion in polar regions and significant O reduction in the marine boundary layer (MBL). Here we use measurement-based modeling to show that, unexpectedly, both RIS and RBS can lead to enhanced O formation in a polluted marine environment under volatile organic compound (VOC)-limited conditions associated with high nitrogen oxide (NO = [NO] + [NO]) concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
(145 reference statements)
0
4
0
Order By: Relevance
“…Nevertheless, possible important effects of INO 3 hydrolysis under high NO x polluted conditions with NO 2 concentrations above 1 ppb have not yet been investigated. Shechner and Tas clearly demonstrated that XNO 3 hydrolysis has a crucial impact on the atmospheric oxidation capacity. Still, their work focused on ozone formation under VOC-limited high NO x conditions, but neglected the influence on Cl activation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, possible important effects of INO 3 hydrolysis under high NO x polluted conditions with NO 2 concentrations above 1 ppb have not yet been investigated. Shechner and Tas clearly demonstrated that XNO 3 hydrolysis has a crucial impact on the atmospheric oxidation capacity. Still, their work focused on ozone formation under VOC-limited high NO x conditions, but neglected the influence on Cl activation.…”
Section: Introductionmentioning
confidence: 99%
“…Still, their work focused on ozone formation under VOC-limited high NO x conditions, but neglected the influence on Cl activation. Shechner and Tas highlighted that improved studies on XNO 3 and especially INO 3 hydrolysis and its effects on atmospheric chemistry are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of reactive halogen compounds as well as of DMS is very sensitive to anthropogenic pollution. The advection of NO x and ozone has strong effects on the activation of reactive halogen compounds (Hoffmann et al, 2019b;Shechner and Tas, 2017;Mahajan et al, 2009b, a;McFiggans et al, 2002) and on DMS oxidation (Breider et al, 2010;Barnes et al, 2006;Chen et al, 2018). Moreover, reactive halogen compounds can significantly influence the depletion of NO x , ozone, SO 2 , volatile organic compounds (VOCs), and oxidized volatile organic compounds (OVOCs) (von Glasow et al, 2002b, a;Sherwen et al, 2017Sherwen et al, , 2016Schmidt et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The chemistry of reactive halogen compounds as well as of DMS is very sensitive to anthropogenic pollution. The advection of NOx and ozone has strong effects on the activation of reactive halogen compounds (Hoffmann et al, 2019b;Shechner and Tas, 2017;Mahajan et al, 2009b;Mahajan et al, 2009a;McFiggans et al, 2002) and on DMS oxidation (Breider et al, 2010; Barnes et al, 2006;Chen et al, 2018). Moreover, reactive halogen compounds can significantly influence the depletion of NOx, ozone, SO2, volatile organic compounds (VOCs), and oxidised volatile organic compounds (OVOCs) (von Glasow et al, 2002b, a;Sherwen et al, 2017;Schmidt et al, 2016;.…”
Section: Introductionmentioning
confidence: 99%